Higher-order fuzzy fractional differential equations: on the existence, uniqueness and Hyers–Ulam–Rassias stability of solutions - Brahim Ghrissi; Abdelkader Amara; Youcef Henka (Journal of Fuzzy Extension and Applications)
In this work, we investigate the existence, uniqueness, and different stability types, focusing on Ulam-Hyers stability, of a solution to a nonlinear fuzzy fractional differential equation with Caputo generalized Hukuhara differentiability of order ℘ ∈ (n − 1, n). We establish explicit criteria to guarantee both the existence and uniqueness of the solution, employing the Banach fixed point theorem. Additionally, we present two examples to enhance the illustration of our findings.